Troxerutin Stimulates Osteoblast Differentiation of Mesenchymal Stem Cell and Facilitates Bone Fracture Healing - Yang, Xiao; Shao, Jiang; Wu, Xiao-Min; Pan, Fei-Fei; Yang, Shao-An; Pan, Xiao-Hua; Jin, An-Min (Frontiers in Pharmacology, 2021)
Troxerutin (TRX), a semi-synthetic derivative of the natural bioflavonoid rutin, is a bioactive flavonoid widely abundant in various fruits and vegetables. Known as vitamin P4, TRX has been demonstrated to have several activities including anti-inflammation, anti-oxidants, vasoprotection and immune support in various studies. Although rutin, the precursor of troxerutin, was reported to have a protective role against bone loss, the function of TRX in skeletal system remains unknown. In the present study, we found that TRX promoted osteogenic differentiation of human mesenchymal stem cells (MSCs) in a concentration-dependent manner by stimulating the alkaline phosphatase (ALP) activity, calcium nodule formation and osteogenic marker genes expression in vitro. The further investigation demonstrated that TRX stimulated the expression of the critical transcription factor β-catenin and several downstream target genes of Wnt signaling, thus activated Wnt/β-catenin signaling. Using a femur fracture rats model, TRX was found to stimulate new bone formation and accelerate the fracture healing in vivo. Collectively, our data demonstrated that TRX could promote osteogenesis in vitro and facilitate the fracture healing in vivo, indicating that TRX may be a promising therapeutic candidate for bone fracture repair.